Analisis Pengendalian Persediaan Obat Antibiotik RSU Haji Medan dengan Menerapkan Metode Always Better Control, Economic Order Quantity, dan Reorder Point - Chairani, Denita; Prasetya, Nurul Huda; Cipta, Hendra (TIN: Terapan Informatika Nusantara, 2021)
Stock out and cito occur because there is no stability between demand for the availability of drugs, it is necessary to control the supply of antibiotics at the Pharmacy Installation of RSU Haji Medan. The purpose of this study is to find out the number of reordering each antibiotic drugs. This research is hold in Pharmacy Installation of RSU Haji Medan. From the results, Always Better Control analysis method showed 63,5% of type A antibiotics, 25,8% of type B antibiotics, and 10,7% of type C antibiotics from the total budgeted users of antibiotics. With the Economic Order Quantity method, the quantity of antibiotic drugs ordered to be optimum includes type A from 2-95 items, type B from 1-107 items, and type C from 0-269 items. With Reorder Point analysis method, the reordered antibiotic drugs included type A from 5-339 items, type B from 1-107 items, and type C from 5-159 items